185k views
1 vote
F(x) = 3x + 10
g(x) = x - 2
Find f(g(5))

1 Answer

4 votes

There are a couple ways we can solve this:

1. We can plug in g into f and then make x = 5


3x+10\\3(x-2)+10\\3x-6+10\\3x+4\\plug.in.5\\3(5)+4\\15+4\\19

So f(g(5)) = 19

2. We can plug in g pre-solved with x = 5 into f


x-2\\5-2\\3\\plug.in.3.into.f\\3x+10\\3(3)+10\\9+10\\19

So again, f(g(5)) = 19

As you can see, either way works fine. it just depends on what makes more sense to you personally.

User Thispatchofsky
by
4.8k points